Long-term coexistence of Pseudomonas aeruginosa and Staphylococcus aureus using an in vitro cystic fibrosis model - Monteiro, R. (2021)
Aim: To investigate the role of pre-established Staphylococcus aureus on Pseudomonas aeruginosa adaptation and antibiotic tolerance. Materials & methods: Bacteria were cultured mimicking the sequential pattern of lung colonization and exposure to ciprofloxacin. Results: In the absence of ciprofloxacin exposure, S. aureus and P. aeruginosa coexisted supported by the physicochemical characteristics of the artificial sputum medium. S. aureus had no role in P. aeruginosa tolerance against ciprofloxacin and did not select P. aeruginosa small-colony variants during antibiotic treatment. rhlR and psqE were downregulated after the contact with S. aureus indicating that P. aeruginosa attenuated its virulence potential. Conclusion: P. aeruginosa and S. aureus can cohabit in cystic fibrosis airway environment for long-term without significant impact on P. aeruginosa adaptation and antibiotic tolerance.